Oil price swings and inflationary echoes: The impact of oil market shocks on consumer and producer prices in Europe and the U.S. - Gago, J.; Vale, S. (Resources Policy, 2025)
This paper empirically investigates the impact of oil price fluctuations on inflation in France, Germany, Portugal, and the United States. Employing a Structural Vector Autoregression (SVAR) model, we analyze the effects of oil supply shocks, global aggregate demand shocks, and oil-specific demand shocks on headline and core inflation as well as the Producer Price Index. Our findings indicate that oil market shocks have non-persistent inflationary effects, with producer prices showing greater volatility compared to consumer prices. The most significant effects stem from oil-specific demand shocks. The study highlights the need for central banks to consider various inflation metrics and the adoption of renewable energies to mitigate the instability caused by oil price swings. The response of each economy to the shocks differs from consumer price and producer price perspectives, revealing the importance of analyzing distinct economic realities and using different inflation measures for more robust conclusions.